2014
DOI: 10.1007/s12072-014-9525-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and comparison of microvessel density using the markers CD34 and CD105 in regenerative nodules, dysplastic nodules and hepatocellular carcinoma

Abstract: MVD determined by CD34 and CD105 expression may be used as an additional parameter to distinguish benign from malignant liver nodules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…In the present study, it was found that CD34 expression in HCC tumor tissue was a risk factor for recurrence. Furthermore, the morphology of VEGFR-2- and CD34-positive cells in HCC tumors reported in previous studies were consistent with those in the current study ( 39 41 ).…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, it was found that CD34 expression in HCC tumor tissue was a risk factor for recurrence. Furthermore, the morphology of VEGFR-2- and CD34-positive cells in HCC tumors reported in previous studies were consistent with those in the current study ( 39 41 ).…”
Section: Discussionsupporting
confidence: 92%
“…Angiogenesis is one of the best known stromal factors participating in tumor progression. [ 15 ] This has been extensively investigated in various tumors such as breast carcinoma,[ 16 ] hepatocellular carcinoma,[ 17 ] astrocytoma,[ 18 ] cervical carcinoma[ 19 ] and ovarian carcinoma. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of angiogenesis that is a proliferative factor for metastasis and tumor growth can be quantified by microvascular density (MVD). e MVD is evaluated by immunohistochemical assay using an endothelial marker (CD34) that is widely used for assessment of angiogenesis in HCC [35,36]. Endothelial cells can be derived from human peripheral CD34-positive cells and contribute to angiogenesis in adults [37].…”
Section: Discussionmentioning
confidence: 99%